2017
DOI: 10.1016/j.jaci.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis: Endotypes, biomarkers, and treatment response

Abstract: It is increasingly recognized that chronic rhinosinusitis (CRS) comprises a spectrum of different diseases with distinct clinical presentations and pathogenic mechanisms. Defining the distinct phenotypes and endotypes of CRS affects prognosis and, most importantly, is necessary as the basis for making therapeutic decisions. The need for individualized definitions of pathogenic mechanisms before initiating therapy extends to virtually all therapeutic considerations. This is clearly crucial with antibiotics, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0
13

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 89 publications
(102 reference statements)
3
85
0
13
Order By: Relevance
“…It is increasingly recognized that CRS comprises a spectrum of conditions with distinct clinical presentations and pathogenic mechanisms. 19 Although CRSsNP is recognized as being predominantly neutrophilic Th1 driven and CR-SwNP as eosinophilic Th2 (high-cytokine IL-4, IL-5, IL-13) driven, there is some overlap between the different phenotypes and endotypes. CRSwNP in Asian populations is driven by Th17 (raised cytokines IL-6, IL-17, and IL-22, tumor necrosis factor-α).…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly recognized that CRS comprises a spectrum of conditions with distinct clinical presentations and pathogenic mechanisms. 19 Although CRSsNP is recognized as being predominantly neutrophilic Th1 driven and CR-SwNP as eosinophilic Th2 (high-cytokine IL-4, IL-5, IL-13) driven, there is some overlap between the different phenotypes and endotypes. CRSwNP in Asian populations is driven by Th17 (raised cytokines IL-6, IL-17, and IL-22, tumor necrosis factor-α).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to antimicrobial properties, some antibiotics have also been found to inhibit different inflammatory pathways as well. For example, doxycycline negatively effects Th2 inflammation, while low‐dose macrolides have been more successful in patients with non‐eosinophilic, neutrophilic inflammation or low IgE CRS . In contrast, topical antibiotics, surfactants and homeopathic treatments such as Manuka honey have not been shown to exert a specific effect on a particular endotype and use of these medications continues to be empiric …”
Section: Discussionmentioning
confidence: 99%
“…In Europe and North America, many studies have shown that the Th2 inflammatory response is predominantly seen in CRSwNP whereas non‐Th2 mediated processes are found more prominently in CRSsNP. However, recent findings have demonstrated that there is in fact a mix of inflammatory processes regardless of polyp status . Non‐Th2 inflammation may be present and have a dominant role in the pathophysiology of both CRSwNP and CRSsNP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the immunopathology and endotypes present in nasal polyposis are diverse, in North America and Europe it is frequently characterized by T2 inflammation. This includes tissue infiltration with eosinophils, mast cells, T and B cells, among other immunocytes, and expansion of tissue-resident populations such as ILC2s 38,39 (Fig 1). Additionally, EpCs produce chemokines and innate type 2 cytokines (TSLP, IL-25, and IL-33), which are variably demonstrated in these patients, [40][41][42][43] highlighting a potential role for EpCs in initiating or perpetuating inflammatory circuits.…”
Section: Diversity Matters: Airway Epithelial Subsets In Health and Pmentioning
confidence: 99%